Shared decision-making in genetic counseling: a scoping review - Chenyang, Peng; Ni, Ning; Yiyu, Li; Xiangmin, Tan; Chaofeng, Tu; Mei, Sun (Acta Bioethica, 2022)
Background: It is challenging to make informed decision in genetic counseling. Shared decision-making provides a chance in balancing the information and preferences between counselors and counselees. However, the status and prescriptions of shared decision-making have not been extensively studied in genetic counseling. Aim: To develop an up-to-date literature review of the shared decision-making in genetic counseling, identify knowledge gaps, and provide inspiration and suggestions for the development and practice of genetic counseling. Methods: “Genetic Counseling” and “Shared decision-making” were used to search in PubMed, Web of Science, Embase, Wanfang, CNKI and CBM databases. The search deadline was March 26, 2021. Results: A total of 22 articles were included, and four themes were identified: how people involved in genetic counseling, different stakeholders involved in SDM, multiple facilitators and barriers to SDM and the effectiveness of SDM in genetic counseling. Conclusion: Each participant needs to recognize their boundaries and make the best effort to involve in the shared decision-making. In the future, multinational studies should be considered for bringing shared decision-making to the global scale and well-designed studies are required to explore the long-term impact of shared decision-making in genetic counseling.